Ekonomi Politik dan Pembangunan Sosial di Kota Merauke: Analisis Peraturan Bupati Merauke Nomor 142 tentang Rencana Umum Penanaman Modal Kabupaten - Haris, Umiyati; Oja, Hubertus (Universitas Musamus, Merauke, Papua, 2024)
This research aims to analyze the implementation of Merauke Regent Regulation No. 142 on the Regency Investment General Plan and its impact on the dynamics of political economy and social development in Merauke City. Using a qualitative research method with descriptive-analytic analysis and data collection through literature study, this study found that the investment policy designed has not run optimally due to constraints in communication, resources, and complex bureaucracy. These factors cause the slow implementation of investment programs in strategic sectors such as agriculture and tourism. In the perspective of policy implementation theory, this study emphasizes the need for improvement in aspects of coordination, bureaucratic structure, and infrastructure support to achieve higher policy effectiveness. The conclusion of this study shows that with proper evaluation and adjustment, investment policy in Merauke has great potential in promoting inclusive economic development and sustainable social welfare. Keywords: Political Economy; Social Development; Public Policy Analysis; Regent Regulation Merauke Regent Regulation No. 142 on the General Plan for Regency Investment